THE DIRECT LEARNING MODEL (EXPLICIT INSTRUCTION) OF NANDAK GANJEN DANCE AT SANGGAR TARI ANYELIR SOUTH JAKARTA - Rahmida Setiawati; Ikrimah Rahmadini (International Journal of Performing Arts (IJPA), 2022)
The direct learning model or Explicit Instruction is a learning model that is carried out directly with the teacher as the giver of the material and the implementer of the learning. This learning model was adopted by Sanggar Anyelir in the Nandak Ganjen Dance training activity. This study aims to obtain data on the process of applying the direct learning model (Explicit Instruction) in the Nandak Ganjen Dance training at Sanggar Anyelir. This research uses descriptive qualitative methods to obtain empirical, clear and in-depth data on the portrait of Nandak Ganjen Dance training at Sanggar Anyelir. This research was conducted from July to September 2020 during the transition period from large-scale restrictions to normal conditions amid the Covid-19 pandemic. The results showed that Nandak Ganjen Dance training through a direct learning model (Explicit Instruction) at Sanggar Anyelir consists of five stages of learning, namely orientation, presentation, structured exercises, guided exercises and independent exercises. In addition, the provision of auditive stimulus in the form of games and motivational provision through dance videos that can encourage students to improve their dancing skills.T